Behavioral swimming effects and acetylcholinesterase activitychanges in Jenynsia multidentata exposed to chlorpyrifos and cypermethrin individually and in mixtures - Bonansea, Rocio Ines (2016)
The pesticides cypermethrin (CYP) and chlorpyrifos (CPF) were found together in water bodies located in agricultural and urban areas. However, the impact to non-target biota from exposure to mixtures has received little attention. In the current study, we evaluated changes in swimming behavior and cholinesterase enzymes activity in Jenynsia multidentata, to investigate the possible effects of these insecticides individually and in mixtures. Moreover, differences between technical and commercial mixtures of the pesticides were evaluated. Females of J. multidentata were exposed over 96 h to CYP (0.04 and 0.4 µg L-1), CPF (0.4 and 4 µg L-1), individually and in a technical and commercial mixtures. Swimming behavior was recorded after 24 h and 96 h of exposure. Also, we measured cholinesterase enzymes activity in brain and muscle after 96 h of exposure. Exposure to CYP increased the exploratory activity of J. multidentata in the upper area of the aquarium. Fish exposed to CPF (4 µg L-1) showed a decrease in swimming activity and an increase in the time spent at the bottom of the aquarium. Interestingly, fish exposed to the technical and commercial mixture of CYP and CPF displayed a different behavior based on the concentration of exposure. Low concentration of pesticides elicited an increase in J. multidentata swimming activity with preference for the upper area of the aquarium, and high concentrations caused decrease in swimming activity with preference for the bottom area of the aquarium. Based on the response of cholinesterase enzymes, acetylcholinesterase in muscle was more sensitive to exposure to CYP, CPF and their mixtures than in brain. A decrease in swimming behavior correlates significantly with the inhibition of acetylcholinesterase activity in muscle of J. multidentata exposed to high concentrations of pesticides. These results draw attention to the need of more studies on the potential ecotoxicological impact of pesticides and its mixtures at environmental relevant concentrations.